2021
DOI: 10.3390/molecules26061521
|View full text |Cite
|
Sign up to set email alerts
|

Peppers: A “Hot” Natural Source for Antitumor Compounds

Abstract: Piper, Capsicum, and Pimenta are the main genera of peppers consumed worldwide. The traditional use of peppers by either ancient civilizations or modern societies has raised interest in their biological applications, including cytotoxic and antiproliferative effects. Cellular responses upon treatment with isolated pepper-derived compounds involve mechanisms of cell death, especially through proapoptotic stimuli in tumorigenic cells. In this review, we highlight naturally occurring secondary metabolites of pepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 212 publications
0
4
0
Order By: Relevance
“…Cellular responses upon treatment with capsaicin affect mechanisms of cell death, especially through the downregulation of β-catenin which plays an important role in β-catenin-dependent signaling that is a significant event in the development of malignancies ( 65 ). In addition, upregulation of pro-apoptotic genes in other words pro-apoptotic stimuli in tumorigenic cells ( 66 , 67 ). Furthermore, one study stated the anti-proliferative effect of capsicum through the suppression of FBI-1-Mediated NF-κB Pathway that led to breast cancer cell apoptosis ( 68 ).…”
Section: Anticancer Activity Of Spices From the Mediterranean Diet: C...mentioning
confidence: 99%
“…Cellular responses upon treatment with capsaicin affect mechanisms of cell death, especially through the downregulation of β-catenin which plays an important role in β-catenin-dependent signaling that is a significant event in the development of malignancies ( 65 ). In addition, upregulation of pro-apoptotic genes in other words pro-apoptotic stimuli in tumorigenic cells ( 66 , 67 ). Furthermore, one study stated the anti-proliferative effect of capsicum through the suppression of FBI-1-Mediated NF-κB Pathway that led to breast cancer cell apoptosis ( 68 ).…”
Section: Anticancer Activity Of Spices From the Mediterranean Diet: C...mentioning
confidence: 99%
“…1 ). Capsaicin exerts analgesic, antioxidant, cardioprotective, anticancer and thermogenic effects, and it can promote weight loss ( 3 ). Some of these effects are mediated by the receptor called ‘transient receptor potential cation channel subfamily V member 1’ (TRPV1), to which capsaicin binds specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids are among the most representative classes of medicinal phytoprinciples and plant secondary metabolites occurring throughout the plant kingdom serving as tools for research and development of new drugs. [ 1 ] Various studies have reported their anticancer activity including cell proliferation inhibition and apoptosis stimulation in cancer cells. [ 2 ] However, the poor hydrophilicity, bioavailability and membrane penetration properties of capsaicin limit its therapeutic activity.…”
Section: Introductionmentioning
confidence: 99%